Doença de Chagas e carcinogênese: influência do interferon-y e GBP-2 - Melo, Marcelo Maia Caixeta de (2014)
Introduction: Chagasic megaesophagus (ME) is associated with a higher occurrence of esophagus cancer, while adenomas and adenocarcinomas are rare in the Chagasic Megacolon (MC). Concentration alterations in some proteins may be associated either with esophagic and colorectal carcinogenesis or with chagasic megacolon and megaesophagus. Objective: Study the association between digestive Chagas disease and carcinogenesis, considering the influence of c-Myc, GBP-2, APC, IFN- and T.cruzi proteins. Material and Method: Blocks of paraffin wax containing fragments of mucous membrane early diagnosed as 1 – normal esophagus (n=16); 2 – chagasic megaesophagus (n=10); 3 – normal colon (n=10) and 4 – chagasic megacolon (n=10) were selected. These tissues were analysed by means of immunohistochemical technique using c-Myc, GBP-2, APC, IFN- and T.cruzi antibodies. Results: The result of the GBP-2 protein expression showed higher positivity in ME (100%) when compared to MC (40%) (p = 0.011). Comparing ME with normal esophagus there was significant difference (p = 0.001), having 100% of positivity for GBP-2 in megaesophagus and 31.3% in normal esophagus. In the analysis of the IFN- expression in MC and normal colon a higher positivity was observed in MC (90%) in relation to normal colon (30%) being the difference significant (p = 0.02). As for the expression of IFN- protein, a higher positivity was observed in MC (90%) in relation to ME (40%). Conclusions: A higher frequency of expression of GBP-2 protein in chagasic megaesophagus and IFN- in chagasic megacolon explains, respectively, the increase of espinocellular carcinoma incidence in patients with chagasic megaesophagus and the protector effect of the chagasic megacolon against the colorectal adenocarcinoma.